Work condition, Exploitation, and Mistreatment of Study of Street Children of Kathmandu Valley - Kunwar, Mala (Nepal Journal of Multidisciplinary Research, 2022)
All vulnerable and homeless individuals congregate on the street. Many people, ranging in age from youngsters to the elderly, can be seen begging on the street. The purpose of this research was to learn more about the working conditions, exploitation, and mistreatment of street children in the Kathmandu valley. The study used a structured questionnaire survey to obtain data from 234 street children. According to the findings, 39.4 percent of street youngsters were begging rather than doing any type of laborious work. 51.3 percent of street children were subjected to misbehavior and harassment by passers-by. Physical, psychological, sexual, and other forms of abuse and mistreatment were perpetrated on street children. The concerned authority should ensure the safety and security of these street children because they have also right of life.